Low back pain - Patrick Raymond Nicolas André Ghislain Stump (Revista Dor)
ABSTRACT BACKGROUND AND OBJECTIVES: Neuropathic pain is present in 37 to 55% of cases of low back pain. Neuropathic pain is associated with more intense pain, more severe comorbidities and worse quality of life. In addition, costs are 67% higher when compared to other etiologies. The purpose of this article is to review this issue that has significant impact on quality of life. CONTENTS: Pain radiating to the lower limb may be radicular or referred pain. Radiation paths of lumbar roots and myofascial trigger points may be very similar, as the root of L5 and gluteus minimus trigger point. Thus, it is essential to use a tool for neuropathic pain assessment, such as: Douleur neuropathique 4 questionnaire, Leeds Assessment of Neuropathic Symptoms and Signs Pain Scale e painDETECT. Clinical history and physical evaluation should formulate diagnostic hypotheses, which should be confirmed with complementary tests when necessary. Guidelines for the treatment of neuropathic pain consider as the first line drugs: anticonvulsants (gabapentin and pregabalin), tricyclic antidepressants (amitriptyline, imipramine, clomipramine and nortriptyline), selective serotonin and norepinephrine reuptake inhibitor (duloxetine and venlafaxine). Second line drugs are: 5% lidocaine patches in localized neuropathic pain and opioids. Surgical treatment of lumbar radiculopathy should be indicated when there is limited or low efficacy of multimodal conservative treatment. CONCLUSION: In low back pain, diagnosis of neuropathic component is critical. Multimodal treatment is imperative, as well as other strategies to rehabilitate and improve the patient's quality of life.